In Situ Vaccination as a Strategy to Modulate the Immune Microenvironment of Hepatocellular Carcinoma - Lurje, Isabella; Werner, Wiebke; Mohr, Raphael; Roderburg, Christoph; Tacke, Frank; Hammerich, Linda (Frontiers in Immunology, 2021)
Hepatocellular Carcinoma (HCC) is a highly prevalent malignancy that develops in patients with chronic liver diseases and dysregulated systemic and hepatic immunity. The tumor microenvironment (TME) contains tumor-associated macrophages (TAM), cancer-associated fibroblasts (CAF), regulatory T cells (Treg) and myeloid-derived suppressor cells (MDSC) and is central to mediating immune evasion and resistance to therapy. The interplay between these cells types often leads to insufficient antigen presentation, preventing effective anti-tumor immune responses. In situ vaccines harness the tumor as the source of antigens and implement sequential immunomodulation to generate systemic and lasting antitumor immunity. Thus, in situ vaccines hold the promise to induce a switch from an immunosuppressive environment where HCC cells evade antigen presentation and suppress T cell responses towards an immunostimulatory environment enriched for activated cytotoxic cells. Pivotal steps of in situ vaccination include the induction of immunogenic cell death of tumor cells, a recruitment of antigen-presenting cells with a focus on dendritic cells, their loading and maturation and a subsequent cross-priming of CD8+ T cells to ensure cytotoxic activity against tumor cells. Several in situ vaccine approaches have been suggested, with vaccine regimens including oncolytic viruses, Flt3L, GM-CSF and TLR agonists. Moreover, combinations with checkpoint inhibitors have been suggested in HCC and other tumor entities. This review will give an overview of various in situ vaccine strategies for HCC, highlighting the potentials and pitfalls of in situ vaccines to treat liver cancer.